(untitled) (Research, Society and Development, 2023)
One of the biggest threats to livestock today is the Rhipicephalus (Boophilus) microplus tick, and this is due to the fact that this ectoparasite causes loss of production and death of animals or is a vector agent of diseases such as bovine parasitic sadness. Another problem currently faced is Dengue, a disease transmitted by Aedes aegypti, which lately has reached high morbidity. In both cases it can be said that one of the main factors that make combat difficult is the resistance that these vectors have acquired to chemical products used to control their populations. The objective of this work was to test the effect of the extract of three aromatic spice plants, namely Salvia rosmarinus, Ocimum basilicum and Origanum vulgare, regarding acaricide activity against B. microplus and regarding larvicidal activity against Ae. aegypti. The vegetables used were purchased in specialized commercial establishments, the collection of engorged females took place in a rural property, in the municipality of Pindamonhangaba - SP and the dipteran larvae were obtained in traps mounted using used kart tires. After carrying out the experiments, mortality was defined after 72 hours, showing the ineffectiveness of the extracts in the acaricide test. However, the extracts of S. rosmarinus and O. basilicum showed satisfactory results as larvicides. Based on the results obtained, it is concluded that the infusions of S. rosmarinus and O. basilicum did not show acaricidal activity against the B. microplus tick and showed larvicidal activity against Ae. aegypti, thus highlighting the applicability of such preparations for the control of populations of this dipteran.